Efficient Extraction of Lithium Ions from High Mg/Li Ratio Brine through the Synergy of TBP and Hydroxyl Functional Ionic Liquids. Issue 12 (17th November 2020) - Bai, Ruibing; Wang, Junfeng; Cui, Li; Yang, Shicheng; Qian, Wei; Cui, Penglei; Zhang, Yanqiang
Summary of main observation and conclusion: The extraction of Li + from the high Mg/Li ratio brine was performed using hydroxyl functional ionic liquids (ILs) as the coextractant and tributyl phosphate (TBP) as the extractant. Firstly, the extractive system, 1‐(2‐hydroxyethyl)‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide ([HOEmim][NTf2 ]) + TBP was proved to exhibit the highest extraction efficiency of Li + (88.15%) from LiCl aqueous solutions among the extractants composed of different ILs, TBP, and ILs + TBP. Effects of various extraction parameters on the extraction efficiencies of Li + and Mg 2+ were then investigated. 95.01% of Li + was extracted and the Li/Mg separation factor reached 405.76 in a single‐stage at 278.15 K and O/A of 2 : 1. The extraction complexes were determined by the slope analysis method and ESI‐MS analysis, and the metal complexes in the organic phase were indicated to be mainly [Li·2TBP][NTf2 ]. The striping study showed that 92.86% of Li + was stripped with 1.0 mol·L –1 HCl. 98% extraction capacity of the synergy extractants was remained after 5 regeneration cycles. The thermodynamic parameters (Δ G °, Δ H °, and Δ S °), together with the mechanism of the Li + extraction were further demonstrated finally. According to the results, [HOEmim][NTf2 ] + TBP extraction system showed promising performance in extracting lithium from salt lake brine with high Mg/Li ratio. Abstract : Based on investigating the effect of various ILs on the extraction efficiency of Li + from LiCl aqueous solutions, [HOEmim][NTf2 ] was selected as the co‐extractant with TBP for the Li + separation from high Mg/Li mass ratio brine.